Exploring The Role and Safety of Autologous Fat Grafting for Breast Augmentation: A Literature Review - Nataatmadja, Beta Subakti; Lumintang, Loelita M; Asmaradianti, Aryunidya; Fabian, Pascalis (The Lingkar Studi Bedah Plastik Foundation and is affiliated with the Department of Plastic Surgery, Faculty of Medicine, Universitas Indonesia., 2025)
Breast augmentation, a commonly sought cosmetic procedure, has shifted towards autologous fat grafting (AFG) as an alternative to implants, primarily due to long-term complications associated with implants. This review aims to provide a comprehensive summary of the autologous fat grafting (AFG) application in breast augmentation surgery. A systematic search strategy was developed for the MEDLINE database and additional articles were identified by reviewing the references. AFG involves harvesting, processing, and injecting the patient's fat into the breast, providing natural results and fewer complications compared to implants. The procedure's success depends on the surgeon's skill. There are challenges and considerations associated with AFG, including volume limitations, variable retention rates, and potential complications such as infections and cyst formation. Uncertainties in fat retention rates influenced by various factors like fat content, processing methods, injection techniques, and patient characteristics, emphasizing the need for further research and careful patient selection.